2014
DOI: 10.7235/hort.2014.13156
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Climate inside Multi-span Plastic Greenhouses under Different Shade Strategies and Wind Regimes

Abstract: In this work, the effects of shade combination, shade height and wind regime on greenhouse climate were quantified. A two-dimensional (2-D) computational fluid dynamics (CFD) model was developed based on an 11-span plastic greenhouse in eastern China for wind almost normal to the greenhouse orientation. The model was first validated with air temperature profiles measured in a compartmentalized greenhouse cultivated with mature lettuce (Lactuca sativa L., 'Yang Shan'). Next, the model was employed to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…These results reaffirm some conclusions already determined in previous works related to the natural ventilation of greenhouses, where it was identified that the renewal indexes are dependent on the ventilation configuration used [68][69][70][71]. It was also identified that there is a linear relationship between the renewal index and wind speed [38,56,72,73], the ventilation configuration that allows to obtain the highest renewal index values is the combined configuration of roof and side vents [10,16,74,75].…”
Section: Renewal Index (Ri)supporting
confidence: 89%
“…These results reaffirm some conclusions already determined in previous works related to the natural ventilation of greenhouses, where it was identified that the renewal indexes are dependent on the ventilation configuration used [68][69][70][71]. It was also identified that there is a linear relationship between the renewal index and wind speed [38,56,72,73], the ventilation configuration that allows to obtain the highest renewal index values is the combined configuration of roof and side vents [10,16,74,75].…”
Section: Renewal Index (Ri)supporting
confidence: 89%